Liver X Receptors Protect Dorsal Root Ganglia from Obesity-Induced Endoplasmic Reticulum Stress and Mechanical Allodynia - Chaitanya K. Gavini; Angie L. Bookout; Raiza Bonomo; Laurent Gautron; Syann Lee; Virginie Mansuy-Aubert (Cell Reports, 2018)
Summary: Obesity is associated with many complications, including type 2 diabetes and painful neuropathy. There is no cure or prevention for obesity-induced pain, and the neurobiology underlying the onset of the disease is still obscure. In this study, we observe that western diet (WD)-fed mice developed early allodynia with an increase of ER stress markers in the sensory neurons of the dorsal root ganglia (DRG). Using cell-specific approaches, we demonstrate that neuronal liver X receptor (LXR) activation delays ER stress and allodynia in WD-fed mice. Our findings suggest that lipid-binding nuclear receptors expressed in the sensory neurons of the DRG play a role in the onset of obesity-induced hypersensitivity. The LXR and lipid-sensor pathways represent a research avenue to identify targets to prevent debilitating complications affecting the peripheral nerve system in obesity. : The mechanism underlying obesity-induced pain is explored by Gavini et al. using cell-specific models. Their analysis reveals that in sensory neurons of the dorsal root ganglia, LXR activation delays western diet-induced ER stress and allodynia. These findings suggest that LXRs in sensory neurons are involved in nociception induced by western diet nutrition. Keywords: liver X receptors, DRG, neuropathy, ER stress, diet-induced obesity